The ostiomioarticular system and its interdisciplinary relationships between Physical Education and the Biological Bases of medicine - Rafael Rousseau Yera; Pedro Javier Lafaurie Rodríguez; Norberto Valcárcel Izquierdo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
In this article we show the different interdisciplinariety relations of Physical education with biological bases of Medicine, in the career of Medicine, where first of all we identify the interdisciplinariety nodes that are related with the ostiomuscular system with the physical activity. This interdisciplinary profile in the formation of students of that career, deserve a place of an important interchange to design the strategies that guaranteeing the integration of knowledge related with the Physical education sciences and Medical sciences.